Oxygen uptake and heart rate during simulated wildfire suppression tasks performed by Australian rural firefighters - Netto, Kevin; Phillips, M.; Payne, W.; Cramer, S.; Nichols, D.; McConell, G.; Lord, C.; Aisbett, B. (2015)
Objective: Australian rural fire crews safeguard the nation against the annual devastation of wildfire. We have previously reported that experienced firefighters identified seven physically demanding tasks for Australian rural fire crews when suppressing wildfires. These firefighters rated the operational importance, typical duration, core fitness components, and likely frequency of the seven tasks. The intensity of these duties remains unknown. The aim of this study was to quantify the oxygen uptake (VO2), heart rate (HR) and movement speed responses during simulations of these physically demanding wildfire suppression tasks. Method: Twenty six rural firefighters (20 men, six women) performed up to seven tasks, during which time their HR and movement speed were recorded. The VO2 for each task was also calculated from the analysis of expired air collected in Douglas bags. Firefighters’ HR and movement speed were measured using HR monitors and portable global positioning system units, respectively. Results: The hose work tasks elicited a VO2 of 21-27 mL·kg-1·min-1 and peak HR of 77-87% age-predicted maximal HR (HRmax). Hand tool tasks were accompanied by VO2 of 28-34 mL·kg-1·min-1 and peak HR of 85-95%HRmax. Firefighters’ movement speed spanned 0.2 ± 0.1 to 1.8 ± 0.2 m·s-1 across the seven tasks. The cardiovascular responses in the hand tool tasks were, in most cases, higher (P < 0.05) than during those elicited by the hose work tasks. Conclusions: The cardiovascular responses elicited during simulations of physically demanding wildfire suppression approximated those reported for similar tasks in urban and forestry fire fighting jurisdictions. The findings may prompt Australian rural fire agencies to consider cardiovascular disease risk screening